"Oh, the Places You'll Go" by Bringing Developmental Science Into the World!. Issue 5 (15th August 2017) - Golinkoff, Roberta M.; Hirsh‐Pasek, Kathy; Grob, Rachel; Schlesinger, Mark
Abstract : Urie Bronfenbrenner and Ernest Boyer argued for leaving the laboratory to conduct rigorous developmental research in the real world where children are found—in the places they go. Contributions to this special issue meet Bronfenbrenner and Boyer's call while at the same time recognizing the continued importance of laboratory research. These articles range from a review of research on the arts to a language intervention in Senegal to large‐scale dissemination and intervention projects designed to communicate the best developmental science to families, public agencies, and schools. Together these articles illustrate how we can study development in the world and enrich our work on the factors that promote development. Taking this path presents us with a set of additional hurdles to be addressed, such as how to communicate with the public and how to scale up our interventions in the face of diversity along many dimensions. Abstract : The title for this Special Section isBringing Developmental Science into the World, edited by Roberta Michnick Golinkoff, Kathy Hirsh‐Pasek, Rachel Grob, and Mark Schlesinger